2022
DOI: 10.3389/fpsyt.2022.950602
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomics of schizophrenia with cognitive impairment: A pilot study

Abstract: Schizophrenia (SCZ) acts as a complex and burdensome disease, in which the functional outcome can be validly predicted by cognitive impairment, as one of the core features. However, there still lack considerable markers of cognitive deficits in SCZ. Based on metabolomics, it is expected to identify different metabolic characteristics of SCZ with cognitive impairment. In the present study, 17 SCZ patients with cognitive impairment (CI), 17 matched SCZ patients with cognitive normal (CN), and 20 healthy control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…An increased ratio of hydroxylated sphingomyelins in pretreatment showed a better reduction of symptoms and increased phosphatidylcholine C38:1, in contrast, suggested poorer response; predictions were improved by incorporating metabolites factors 46. Our previous research also supported metabolomics has potential in biomarkers exploration related to the diagnosis and treatment of mental disorders 47 48. In addition, emerging fields, known as epigenomics and microbiome, have shown some degree of association with prognosis 49–52…”
Section: Introductionsupporting
confidence: 54%
“…An increased ratio of hydroxylated sphingomyelins in pretreatment showed a better reduction of symptoms and increased phosphatidylcholine C38:1, in contrast, suggested poorer response; predictions were improved by incorporating metabolites factors 46. Our previous research also supported metabolomics has potential in biomarkers exploration related to the diagnosis and treatment of mental disorders 47 48. In addition, emerging fields, known as epigenomics and microbiome, have shown some degree of association with prognosis 49–52…”
Section: Introductionsupporting
confidence: 54%
“…We performed targeted metabolomics profiling for fecal and serum samples by an ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) system (ACQUITY UPLC-Xevo TQ-S, Waters Corp., Milford, MA, 570 USA). The Q300 Kit provided by Metabo-Profile Corp. (Shanghai, China), coving up to 310 metabolites and 12 biochemical classes, was used for targeted metabolomics profiling, which was commonly used in several recent studies [43][44][45] . It mainly includes known gut microbiota-derived metabolites including SCFAs, bile acids, indoles, etc.…”
Section: Fecal and Blood Metabolomics Profiling And Preprocessingmentioning
confidence: 99%
“…Imbalances in the cystine/glutamate ratio can lead to physiological disorders [ 30 ]. This study also found elevated glutamate levels in both Miao and Han SCZ patients [ 31 ], suggesting a more significant change in the cystine/glutamate ratio among the Miao population [ 32 ]. This raises the question of whether there is an ethnic difference in the expression of the cystine/glutamate antiporter, warranting further exploration.…”
Section: Discussionmentioning
confidence: 80%